Percutaneous Pedicle Screw Stabilization: Surgical Technique, Fracture Reduction, and Review of Current Spine Trauma Applications. Issue 7 (1st April 2018) - Alander, Dirk H.; Cui, Shari
Abstract : Percutaneous pedicle screw fixation has evolved as a useful tool in the management of spinal trauma. As a minimally invasive approach, it provides the stability of open instrumentation while limiting blood loss, avoiding excessive muscle/soft-tissue insult, and improving postoperative pain and mobilization. Muscle-dilating techniques also preserve greater paraspinal muscle volume and strength compared with open midline approaches. In patients with spinal trauma, the use of percutaneous instrumentation and indirect reduction can theoretically preserve the fracture hematoma and its osteogenic inflammatory factors. The evolution of spinal instrumentation and the refinement of indirect reduction techniques has improved the capacity for correction of traumatic deformity. Although perioperative and short-term results have been well described, few long-term outcomes data exist.